THE ROLE OF ACTIVE TEACHING METHODS IN LANGUAGE PREPARATIONS FOR FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2003)
The article is devoted to the problem o f using active methods of teaching in Higher Institutions which ensure better results of language training of future teachers. Special attention is payed on such active methods as business game,discussion.